2013
DOI: 10.1089/ars.2012.5026
|View full text |Cite
|
Sign up to set email alerts
|

May Serum Levels of Advanced Oxidized Protein Products Serve as a Prognostic Marker of Disease Duration in Patients with Idiopathic Parkinson's Disease?

Abstract: Protein and amine halogenation is a type of oxidative stress induced by phagocytic overstimulation, and its role in Parkinson's disease (PD) has not been discerned. We have detected that advanced oxidized protein products, markers of protein halogenation, are reliably enhanced in serum of patients with PD (n=60) relative to control subjects (n=45, p<0.012), and to a lesser extent in the cerebrospinal fluid. Amine halogenation, as evaluated through 3-chlorotyrosine, is not affected. Mieloperoxidase and hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…Garcia‐Moreno et al showed, through enzyme‐linked immune assays (ELISA) that the amount of advanced oxidized protein products (AOPP, a marker for protein halogenation which is the result of free radicals) in CSF increased significantly faster in incubated CSF from PD patients with Hoehn & Yahr (H&Y) score 1–2 compared with H&Y score 3–4 and controls, maybe indicating a susceptibility to oxidative damage in early disease stages. Corroborating this notion, Fernandez et al showed an increase in unspecific 3‐nitrotyrosine protein products (nitrosylation of proteins being an oxidative damage mechanism) in PD patients with H&Y score 1–2 compared with advanced PD and controls.…”
Section: Resultsmentioning
confidence: 99%
“…Garcia‐Moreno et al showed, through enzyme‐linked immune assays (ELISA) that the amount of advanced oxidized protein products (AOPP, a marker for protein halogenation which is the result of free radicals) in CSF increased significantly faster in incubated CSF from PD patients with Hoehn & Yahr (H&Y) score 1–2 compared with H&Y score 3–4 and controls, maybe indicating a susceptibility to oxidative damage in early disease stages. Corroborating this notion, Fernandez et al showed an increase in unspecific 3‐nitrotyrosine protein products (nitrosylation of proteins being an oxidative damage mechanism) in PD patients with H&Y score 1–2 compared with advanced PD and controls.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, we speculate that oxidative DNA damage plays a significant role in the pathogenesis of PD. Therefore, the 8-OHdG levels in the CSF and serum of PD patients are significantly higher than normal controls (Gmitterová et al, 2009 ; Isobe et al, 2010 ; García-Moreno et al, 2013 ). Furthermore, the concentrations of 8-OHdG are positively associated with the duration of illness and %CoQ-10 (Isobe et al, 2010 ).…”
Section: Biochemical Biomarkersmentioning
confidence: 99%
“…Five ml of CSF was collected and stored in polypropylene tubes (Eurotube), and rapidly aliquoted, coded, and frozen at -80°C for further analyses. A 1-ml collection in a glass tube was em-ployed to observe the absence of traumatic puncture and to quantify red cells before storing (3). CSF with excess of red cells was discarded ( > 500 red cells/ll).…”
Section: Blood and Csf Collection And Biochemical Measuresmentioning
confidence: 99%